2013
DOI: 10.1186/1471-2393-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and delivery practice in a Vietnamese rural district during 12 year of rapid economic development

Abstract: BackgroundSince the Doi Moi reform 1986 economic conditions in Vietnam have changed significantly and positive health and health care developments have been observed. International experience shows that improved economic conditions in a country can reduce the risk of perinatal mortality, decrease the risk of low birth weight and increase the mean birth weight in newborns. The Health and Demographic Surveillance Site (HDSS) FilaBavi in Bavi district outside Hanoi city has been operational since 1999. An open co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…16 We found that the use of Cesarean section increased in our periurban settings along with economic growth and availability of services. This is in accordance with the results from previous studies in urban areas in Vietnam 10,17 and other Asian countries. Vietnam is the country with the second highest Cesarean section rate in Asia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…16 We found that the use of Cesarean section increased in our periurban settings along with economic growth and availability of services. This is in accordance with the results from previous studies in urban areas in Vietnam 10,17 and other Asian countries. Vietnam is the country with the second highest Cesarean section rate in Asia.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings, however, show that the overall mean birth weight had been stable over the years in spite of a rather drastic economic development in the study areas. This finding agrees with one recent longitudinal survey in a rural district in Hanoi 10 but disagrees with other previous studies in Vietnam, and other countries, which report a significant increase in the mean birth weight over time with economy growth. 11,12 Notably, this result is consistent with a report in the United States where the mean birth weight also decreased from 1990 to 2005.…”
Section: Discussionsupporting
confidence: 69%
“…There are indications that sex-ratio imbalance has grown in many South Asian, Central Asian, and East Asian countries in the recent decades as a result of preference for the male child and sex selection ( 26 ). A trend towards increasing imbalance in SRB ( 13 ) from the biological value of 105 has been documented in Vietnam since the year 2000 ( 13 – 15 ), reaching 110.6 at the 2009 census ( 13 ). An elevated SRB was also demonstrated in the Quang Ninh province in northern Vietnam during the years 2008–2011, with large differences in SRB depending on both place and mode of delivery ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding likely stems from the enactment of the one-or-two child policy in Vietnam in the late 1980s [ 17 , 19 ]. Another two population studies [ 20 , 21 ] conducted in urban and suburban areas of Hanoi also reported a difference in the CS rate between male and female children. Hence, these authors concluded that high income and differences in the CS rates between the sexes might be related to requests made for CS without medical needs [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 94%